KHAZANAH LEKSIKON TUMBUHAN BERKHASIAT DALAM BAHASA MELAYU DIALEK SANGGAU - Lili Redia Fahmi; Sisilya Saman Madet; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractEfficacious plants are plants that have uses for national medicine and customs that are distinctive, special, and special to refer to a particular purpose. This study examined the form of lingual lexicon units, lexicon meanings, and efficacious lexicons that produce computerized lingusitic application and produce learning material supplements in the form of text and text structures for class VII of the 2013 junior high school revised edition 2017. The method used in this study was a descriptive method with a qualitative research. Based on the results of data analysis, 116 collections of plant lexicons were efficacious in the Malay language Sanggau dialect. Plant lexicons efficacious in this study consisted of 62 words and 54 phrases. The overall plant Lexicon has a lexical meaning of 113 lexicons and 3 lexicons defining it directly from the observations of these plants and resulting in the application of computerized linguistic Weses and supplementary learning materials in the form of text and text structures namely observation text, exposition text, description text and procedure text for the seventh grade of the 2013 revised curriculum for the 2013 Middle School. Keywords: Lexicon, Nutritious Plants, Treasure, Wesay, Wearning Supplements